Role of Coupled Domain Motions on the Catalytic Activity of Escherichia coli Prolyl-tRNA Synthetase. - Cao, Bach; Greene, Alexander J.; Zimmerman, Kurt A. (My University, 2009)
Prolyl-tRNA synthetases (ProRSs), which are class II synthetases that catalyze covalent attachment of proline to the 3'end of the tRNAPro. ProRSs from all three kingdoms of life, have shown to misactivate noncognate alanine and cysteine, and form mischarged aminoacyl?tRNAPro. It has been found that the insertion domain (?180 amino acids) of Escherichia coli (Ec) ProRS is the post-transfer editing active site that hydrolyzes specifically mischarged alanyl-tRNAPro. Herein, we report the effect of mutations on highly conserved residues (G217 and E218) located on the loop connecting the catalytic and editing domains of Ec ProRS.
Color poster with text, images, chart and diagrams.
Keywords: Posters; Catalytic RNA; Escherichia coli; Ligases